Choroid plexus volume in multiple sclerosis predicts expansion of chronic lesions and brain atrophy. Issue 10 (3rd September 2022) - Klistorner, Samuel; Barnett, Michael H.; Parratt, John; Yiannikas, Con; Graham, Stuart L.; Klistorner, Alexander
Abstract: Objectives: Recent studies suggested that the expansion of long‐standing multiple sclerosis (MS) lesions and an enlargement of choroid plexus may be linked to chronic inflammation and microglial activation. We investigated the potential association between plexus volume and subsequent lesion expansion in patients with relapsing‐remitting MS. Methods: Pre‐ and post‐gadolinium 3D‐T1, 3D FLAIR and diffusion tensor images were acquired from 49 patients. Choroid plexus (CP) volume (normalised by Total Intracranial Volume, TIV) and lesion activity were analysed between baseline and 48 months. In addition, plexus volume was measured in 40 healthy controls of similar age and gender. Results: Baseline CP/TIV ratio was significantly larger in RRMS patients compared to normal controls ( p  < 0.001). CP/TIV ratio remained stable in RRMS patients during follow‐up period. There was a strong correlation between baseline CP/TIV ratio and subsequent rate of chronic lesion expansion ( p  < 0.001), which was stronger in close proximity to CSF. A cut‐off of 98 × 10 −5 CP/TIV ratio predicted future lesion expansion with a sensitivity of 85% and specificity of 76%. CP/TIV ratio larger than a cut‐off was associated with >8‐fold increased risk of chronic lesion expansion. Baseline CP/TIV ratio was also associated with change in Mean Diffusivity (MD) inside of chronic lesions. Furthermore, baseline CP/TIV ratio significantly correlated with central brain atrophy. There was, however, no correlation between CP/TIV ratio and volume of new lesions. Interpretation: Our data demonstrate that baseline CP/TIV ratio predicts subsequent expansion of chronic periventricular MS lesions and associated tissue damage within and outside of chronic lesions.